Computing the Hosoya and the Merrifield-Simmons Indices of Two Special Benzenoid Systems - Öz, Mert Sinan; Cangul, Ismail Naci (University of Kashan, 2021)
Gutman et al. gave some relations for computing the Hosoya indices of two special benzenoid systems Rn and Pn. In this paper, we compute the Hosoya index and Merrifield-Simmons index of Rn and Pn by means of introducing four vectors for each benzenoid system and index. As a result, we compute the Hosoya index and the Merrifield-Simmons index of Rn and Pn by means of a product of a certain matrix of degree n and a certain vector.
Keywords: Benzenoid systems; Hexagonal systems; Hosoya index; Merrifield-Simmons index